A Analisis Pengaruh Strategi Flash Sale Terhadap Minat Beli dan Perilaku Impulsif Mahasiswa ITS - Noverita Rizki Pramesta; Cecilia Melva Natania; Awliya Hanun Izdihar; Nur Aini Rakhmawati (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
In this era of digitalization, many things can be done easily thanks to the help of technology. One of these things is buying and selling, which now no longer must come to the store to buy goods. Only by relying on smartphones, people can buy and sell a product on e-commerce. In addition, there are also many attractive offers provided by e-commerce, one of which is a flash sale which will give you product prices on certain days. Of course, this is done as a marketing strategy to attract people's buying interest in the store, not infrequently for student consumers. However, this can also result in the impulsive behavior of consumers in purchasing e-commerce products. This study aims to determine how the flash sale strategy influences the buying interest and impulsive behavior of consumers, especially ITS students. This study uses a convergent validity test based on the value of factor loading and Average Variance Extracted and a reliability test based on the value of composite reliability and Cronbach's alpha. Then, analyzed by r-square value and Path Coefficient test. The results of data processing showed that trust in products and flash sale programs influenced consumer buying interest which could encourage consumer impulsive buying behavior in ITS student consumers. Keywords: flash sale, e-commerce, buying interest, university students, impulsive behavior